Correlations between the iodine concentrations from dual energy computed tomography and molecular markers Ki-67 and HIF-1α in rectal cancer: A preliminary study. Issue 96 (November 2017) - Fan, Shuxuan; Li, Xubin; Zheng, Lei; Hu, Dongzhi; Ren, Xiaoyi; Ye, Zhaoxiang
Abstract: Purpose: To investigate whether dual energy computed tomography (CT) with iodine quantification is correlated with molecular markers Ki-67and hypoxia-inducible factor 1α (HIF-1α)in rectal cancer (RC). Materials and methods: Eighty patients (43 males and 37 females) diagnosed with rectal cancer got pelvic contrast-enhanced CT scan with dual energy computed tomography before any anticancer treatment. Analyse the normalized iodine concentration (NIC) values and CT values at each energy level (40–140 keV) from the virtual monochromatic image of the primary lesions. The postoperative specimens of all 80 patients underwent Ki-67 and HIF-1α immunohistochemistry staining. By SPSS17.0 software package, we analyzed the correlations of NIC values and CT values at each energy level (40–140 keV) with Ki-67 and HIF-1α expression. The receiver operating characteristic (ROC) curves of these dual energy computed tomography parameters were calculated and the diagnostic value were assessed. Results: There was a weak positive correlation between NIC values and carcinoembryonic antigen level (r = 0.246, P = 0.028) in RC. Both the value and the level of Ki-67 expression were correlated positively with the NIC values (r = 0.344, P = 0.002 and r = 0.248, P = 0.026). HIF-1α expression was correlated positively with the NIC values of the RC (r = 0.598, P < 0.001). The best threshold values of NIC values in diagnosing the expression of HIF-1α was 0.5839. The sensitivity, 78%; specificity, 87%; PPV, 86%; NPV, 79%;accuracy, 83%. Conclusion: The NIC values on dual energy computed tomography may be used as a measurement of hypoxia in RC and determining the ability of tumor invasion noninvasively.